PERSEPSI PETANI TERHADAP PELAKSANAAN PEREMAJAAN KELAPA SAWIT RAKYAT (STUDI KASUS : DESA KAMPUNG BARU, KECAMATAN BILAH BARAT, KABUPATEN LABUHANBATU) - Mahendra, Muhammad Wifrizal; Rozalina, Rozalina; Saragih, Faoeza Hafiz (MEDIAGRO, 2024)
This research was conducted in Kampung Baru Village, West Bilah District, Labuhanbatu Regency with the research title "Farmers' Perceptions of the Implementation of People's Oil Palm Rejuvenation (Case Study: Kampung Baru Village, West Bilah District, Labuhanbatu Regency)" in August 2022. The purpose of this research is to analyze how farmers' perceptions of the implementation of community oil palm rejuvenation in the research area of Kampung Baru Village. The data collected in this study consisted of primary data and secondary data. Primary data was obtained from information provided by farmers as respondents using a list of questions (questionnaire) that had been prepared beforehand. Secondary data is data obtained from information from related institutions and book literature related to this research, then analyzed using descriptive qualitative data. The results of this study indicate that Farmers' Perceptions of the Implementation of People's Oil Palm Rejuvenation (Case study: Kampung Baru Village, West Bilah District, Labuhanbatu Regency), from the economic aspect, have a neutral perception, while the social and technical aspects have very good perceptions.Keywords: Farmers' Perceptions of the Implementation of Oil Palm Rejuvenation